2002
DOI: 10.1124/jpet.102.033886
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Actions of (S)-Desmethylzopiclone (SEP-174559), an Anxiolytic Metabolite of Zopiclone

Abstract: This study set out to profile the activity of (S)-desmethylzopiclone (SEP-174559) at subtypes of the ␥-aminobutyric acid type-A (GABA A ) receptor and other neurotransmitter receptor ion channels. Recombinant receptors were expressed in human embryonic kidney 293 cells and examined functionally by patch-clamp recording with fast perfusion of agonist and drug solutions. Micromolar concentrations of SEP-174559 potentiated GABA A receptor currents evoked by subsaturating concentrations of GABA. The potentiation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…However, noncompetitive modulation has been demonstrated in many systems (e.g., Maelicke and Albuquerque, 2000;Levandoski et al, 2003;Broad et al, 2006). Likewise, SEP-174559 inhibits rat ␣3␤4 noncompetitively, but without the voltage dependence expected for a channel blocker (Fleck, 2002), which was also observed for clozapine block of ␣7 receptors (Singhal et al, 2007). We are intrigued by the possibility that disparate ligands act through a common type of binding site.…”
Section: Nicotinic Receptor Potentiation By Improved Gating 473mentioning
confidence: 99%
“…However, noncompetitive modulation has been demonstrated in many systems (e.g., Maelicke and Albuquerque, 2000;Levandoski et al, 2003;Broad et al, 2006). Likewise, SEP-174559 inhibits rat ␣3␤4 noncompetitively, but without the voltage dependence expected for a channel blocker (Fleck, 2002), which was also observed for clozapine block of ␣7 receptors (Singhal et al, 2007). We are intrigued by the possibility that disparate ligands act through a common type of binding site.…”
Section: Nicotinic Receptor Potentiation By Improved Gating 473mentioning
confidence: 99%
“…93). Subsequently, a closer examination of the Senantiomer of the N-desmethyl metabolite showed that it possesses pharmacological activity by binding better to GABA A receptors possessing the g2 subunit (Fleck, 2002). Nevertheless, after administration of zopiclone, neither the N-oxide nor desmethyl metabolites are detected in plasma (Fernandez et al, 1993), and Pharmacologically Active Metabolites therefore, it is unlikely that any drug-related effect in vivo can be attributed to metabolites.…”
Section: Drugs With Metabolites That Possess Target Potency But Comentioning
confidence: 99%
“…However, another report showed little subunit selectivity for zopiclone and reported mixed affinities for zaleplon on ␣ subunits depending upon which ␥ subunits they were combined with (Damgen and Luddens, 1999). Electrophysiological recordings were used to determine the K d of (R,S)-zopiclone from kinetics (K d ϭ k off /k on ) using a single concentration of zopiclone (20 M) (Fleck, 2002). GABA A receptors containing ␣1 subunits have been shown to mediate the sedative effects of diazepam (Rudolph et al, 1999;Low et al, 2000;McKernan et al, 2000) and zolpidem .…”
mentioning
confidence: 99%